Lung and gastrointestinal complications are leading causes of death in SCORE, a multi-ethnic Singapore systemic sclerosis cohort. (1st November 2016) - Santosa, A; Tan, CS; Teng, GG; Fong, W; Lim, A; Law, WG; Chan, G; Ng, SC; Low, AHL
Abstract : Objectives : To assess contemporary outcomes and predictors of mortality in the well-characterized multi-ethnics ystemic sc lerosis co hort Singapore (SCORE). Method : From 2008, patients diagnosed with systemic sclerosis (SSc) fulfilling the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) or Very Early Diagnosis of Systemic Sclerosis (VEDOSS) criteria were recruited from three major tertiary rheumatology centres in Singapore. Mortality was verified with the Singapore National Registry of Deaths and in-hospital cause of death was determined by two independent reviewers, up to 10 December 2013. A Cox proportional hazard (PH) regression analysis was used to examine the association between demographic and clinical indices and mortality, controlling for age and race. Results : Of the 349 patients (86.8% female; 77.7% Chinese), 97.4% fulfilled the ACR/EULAR 2013 criteria. The mean age at diagnosis was 46.2 years. The prevalence of limited (lcSSc), diffuse (dcSSc) cutaneous SSc, and SSc-overlap syndromes was 34.4, 37.1, and 26.8%, respectively. Thirty-five patients died after a mean follow-up of 2.1 years (743.6 person-years). Fifty-seven per cent of deaths were attributed to SSc, with pulmonary arterial hypertension (PAH), interstitial lung disease (ILD), and gastrointestinal (GI) complications as the leading causes of death. Multivariate analysis (n = 275) showed that smoking [hazard ratio (HR) 4.0, 95% confidence interval (CI) 1.5–10.6], SSc-overlap (HR 6.0, 95% CI 1.8–19.1), baseline renal involvement (HR 2.5, 95% CI 1.1–6.0), pulmonary artery systolic pressure (PASP) ≥ 40 mmHg on echocardiography (HR 5.1, 95% CI 2.2–11.7), treatment for peripheral vasculopathy (HR 2.6, 95% CI 1.1–6.5), and parenteral nutrition (HR 8.8, 95% CI 2.2–34.3) were independent predictors of mortality. Conclusions : PAH, ILD, and GI complications were leading causes of death in this cohort. We identified a high-risk group of patients who would benefit from closer monitoring and early intervention.